Monnaies flottantes, or et DTS : Quelques aspects juridiques nouveaux. (Pamphlet Series, 1976)
This paper outlines legal developments related to floating currencies, gold, and special drawing rights (SDRs) in the IMF. The Articles of the Fund require each member to establish a par value for its currency in terms of gold as a common denominator. Alternatively, the par value may be expressed in terms of the U.S. dollar of the weight and fineness in effect on July 1, 1944, the effect of which is simply to express the par value indirectly in terms of gold. In this paper, application of existing provisions and valuation of the SDR are discussed in detail, and the new provisions and practices are also elaborated.